Dysfunctional sleep beliefs and sleep quality among Chinese university students: the mediating roles of depression, anxiety, and stress - Peisi Wang; Chun Xie; Jiali Qian; Shaobo Cai; Lei Xu; Xianyong Jiang; Guozhuang Chen; Kun Wang (BMC Psychology)
Abstract Background Sleep problems faced by college students have become an important global health issue that requires immediate attention. This study investigates the relationship between dysfunctional beliefs and attitudes about sleep (DBAS) and sleep quality among college students, with a focus on examining the mediating effects of anxiety, stress, and depression in this relationship. Methods A cross-sectional design was employed, with data collected through a survey conducted from January to March 2024 among Chinese university students. The survey evaluated DBAS, anxiety, depression, stress, and sleep quality. Descriptive statistics and correlation analysis were performed using SPSS 27.0, subsequently applying PROCESS models (Model 4 and Model 6) to develop parallel and chain mediation models. Results A total of 864 valid responses were retained, comprising 629 male participants (72.8%) and 235 female participants (27.2%), with ages ranging from 16 to 23 years (M = 18.8, SD = 1.0). The findings demonstrated that DBAS negatively predicted sleep quality (B = − 0.15, 95% CI [− 0.20, − 0.09]). Anxiety (B = − 0.03, 95% CI [− 0.06, − 0.01]) and stress (B = − 0.05, 95% CI [− 0.08, − 0.02]) performed as parallel mediators in the association between DBAS and sleep quality. Furthermore, DBAS influenced sleep quality indirectly through the chain mediation of anxiety and stress (β = −0.04, 95% CI [− 0.07, − 0.02]). Conclusions DBAS has a direct negative impact on sleep quality and affects it indirectly through the parallel mediation of anxiety and stress. Additionally, DBAS may indirectly influence sleep quality through the chain-mediating effects of anxiety and stress. The study highlights the significance of addressing DBAS, as it directly affects students’ emotional well-being and sleep quality. Future research should concentrate on creating targeted interventions to reduce DBAS, thus enhancing emotional health and sleep quality in university students.